Out with the Old, In with the New? Habitus and Social Mobility at Selective Colleges. (January 2013) - Lee, Elizabeth M.; Kramer, Rory
Sociologists have long recognized that cultural differences help explain the perpetuation of inequality by invisibly limiting access to elite cultural norms. However, there has been little investigation of the ways students reconcile shifts in habitus gained in educational settings with existing, nonelite habitus. The authors use both qualitative and quantitative data to examine the ways students navigate what Bourdieu called a "cleft habitus." In particular, the authors examine how students of low socioeconomic status experience contacts with their families and hometown friends, arguing that these moments are crucial to understanding whether and how their habitus is changing and whether that change creates a divide between those students and their origins. Interview and survey data both show that social mobility does not come without sacrifice and that these sacrifices warrant more serious study in the sociology of stratification.